Unusually complex phase of dense nitrogen at extreme conditions. Issue 1 (December 2018) - Turnbull, Robin; Hanfland, Michael; Binns, Jack; Martinez-Canales, Miguel; Frost, Mungo; Marqués, Miriam; Howie, Ross; Gregoryanz, Eugene
Abstract Nitrogen exhibits an exceptional polymorphism under extreme conditions, making it unique amongst the elemental diatomics and a valuable testing system for experiment-theory comparison. Despite attracting considerable attention, the structures of many high-pressure nitrogen phases still require unambiguous determination. Here, we report the structure of the elusive high-pressure high-temperature polymorphι –N2 at 56 GPa and ambient temperature, determined by single crystal X-ray diffraction, and investigate its properties using ab initio simulations. We find thatι –N2 is characterised by an extraordinarily large unit cell containing 48 N2 molecules. Geometry optimisation favours the experimentally determined structure and density functional theory calculations findι –N2 to have the lowest enthalpy of the molecular nitrogen polymorphs that exist between 30 and 60 GPa. The results demonstrate that very complex structures, similar to those previously only observed in metallic elements, can become energetically favourable in molecular systems at extreme pressures and temperatures. Nitrogen has a complex phase diagram with rich polymorphism, which is challenging to characterize due to the extreme conditions and uncertain stability ranges needed to do so. Here the authors resolve one of the most elusive phases of this model system, reporting a crystalline structure with unusual complexity.